2017
DOI: 10.1016/j.jcin.2016.10.023
|View full text |Cite
|
Sign up to set email alerts
|

Apixaban in Patients With Atrial Fibrillation After Transfemoral Aortic Valve Replacement

Abstract: In patients undergoing TAVR, AF was associated with a significantly higher rate of all-cause mortality throughout 12 months follow-up. The early safety endpoint in patients with AF on apixaban was significantly less frequent compared with patients receiving a VKA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
95
1
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(101 citation statements)
references
References 25 publications
1
95
1
4
Order By: Relevance
“…According to a study of TAVI for AS complicated by atrial fibrillation, safety end points specified in the VARC-2 criteria (a composite of all-cause mortality, all strokes, life-threatening bleeding, acute kidney injury, coronary obstruction, major vascular complications and valve dysfunction requiring reintervention) were reached by a smaller number of patients using apixaban postoperatively than by those using warfarin 29. An international, randomised, open-label, event-driven, phase III trial, the GALILEO study (Global Study Comparing a rivaroxaban based Antithrombotic Strategy to an antiplatelet based Strategy After Transcatheter aortic valve rEplacement to Optimise Clinical Outcomes, NCT02556203) is currently underway in an attempt to determine whether rivaroxaban is capable of preventing major cardiovascular events.…”
Section: Treatmentmentioning
confidence: 99%
“…According to a study of TAVI for AS complicated by atrial fibrillation, safety end points specified in the VARC-2 criteria (a composite of all-cause mortality, all strokes, life-threatening bleeding, acute kidney injury, coronary obstruction, major vascular complications and valve dysfunction requiring reintervention) were reached by a smaller number of patients using apixaban postoperatively than by those using warfarin 29. An international, randomised, open-label, event-driven, phase III trial, the GALILEO study (Global Study Comparing a rivaroxaban based Antithrombotic Strategy to an antiplatelet based Strategy After Transcatheter aortic valve rEplacement to Optimise Clinical Outcomes, NCT02556203) is currently underway in an attempt to determine whether rivaroxaban is capable of preventing major cardiovascular events.…”
Section: Treatmentmentioning
confidence: 99%
“…Prospective studies such as GALILEO , ATLANTIS (http://clinicaltrials.gov identifier NCT02664649) and ENVISAGE‐AF TAVI (http://clinicaltrials.gov identifier NCT02943785) will determine the role of non‐vitamin K antagonists compared with VKA in TAVR patients including those with new‐onset AF . One recent study was encouraging for apixaban use in TAVR, which showed lower risk of bleeding with similar incidence of ischemic outcomes compared to warfarin use .…”
Section: Discussionmentioning
confidence: 99%
“…Another significant post‐TAVR concern is NOAF, with an incidence of 9.1% to 31.9% in various reports . The arrhythmia tends to occur 24–48 hours post TAVR, with a duration of approximately 24 hours in the majority of patients . Larger left atrial size (> 27 mm/m 2 ) and transapical approach to valve placement have been identified as risk factors for NOAF.…”
Section: Nodal Blocking Agent Managementmentioning
confidence: 99%
“…20,44 The arrhythmia tends to occur 24-48 hours post TAVR, with a duration of approximately 24 hours in the majority of patients. 35,53 Larger left atrial size (> 27 mm/m 2 ) and transapical approach to valve placement have been identified as risk factors for NOAF. In the absence of guidelines or randomized controlled trials specific to prevention or management of atrial fibrillation after TAVR, clinicians should consider deferring to existing guidelines for patients undergoing SAVR.…”
Section: Prevention and Treatment Of Tavr Infective Endocarditismentioning
confidence: 99%